Thermochemical behavior of eucalyptus grandis wood exposed to termite attack - Gallio, Ezequiel; Römer Schulz, Henrique; Guerreiro, Laíse; Dias Cruz, Nidria; Zanatta, Paula; Pinto da Silva Júnior, Mário Antônio; Alberto Gatto, Darci (Maderas. Ciencia y Tecnología, 2020)
This study aimed to evaluate the variations in thermal and chemical characteristics of juvenile Eucalyptus grandis wood submitted to a deterioration test by Nasutitermes termites. For this purpose, a biodeterioration test with termites was conducted according to ASTM D 3345 (2008), in which, after the end of the period corresponding to the test (40 days), we evaluated the mass loss, chemical composition and thermal stability of the main components of the deteriorated wood samples and those belonging to the control group. We found that deterioration due to exposure of the samples to Nasutitermes sp. termites caused a mass loss of 66.88% for wood with a density at 12% moisture content of 0.412 g.cm-3. The quantitative chemical composition showed a reduction in the contents of cellulose, hemicellulose and lignin. Analysis of the variations of the organic functional groups related to the chemical composition of the wood by Fourier Transform Infrared Spectroscopy and relative intensity of the spectral bands also showed reductions, demonstrating homogeneous deterioration of the main components of the deteriorated woods. The thermal stability showed an increase in deteriorated wood for most of the temperature ranges, mainly for those that corresponded to losses in moisture and volatiles (25 °C - 100 °C), hemicelluloses (240 °C - 300 °C), celluloses, and together with initial lignin degradation (310 °C to 400 °C), possibly due to the removal of cellulose and hemicellulose, as well as the deposition of substances expelled by the termites in the cell wall. From the results, we conclude that the termites do not have specificity regarding the chemical component and that the deterioration caused variations in the chemical composition of the wood, whereas the opposite was observed for thermal stability, which presented an increase in most of the temperatures ranges for the deteriorated woods compared to the control group.